Contact improvisation today Josephine Leask at Chisenhale's conference on contact improvisation - Leask, Josephine (Dance Books Ltd., Alton,Hampshire (UK), 1998)
They thought contact improvisation constituted a kind of exclusive religious sect, attracting baggy-trousered, cheesecloth-shirted, white, college-educated New Age thirty- to fifty-yer-old. PALABRAS CLAVE: contemporary dance, contact improvisation, Steve Paxton, Kevin Finnan, jam, Mary Prestidge.